PERILAKU SELF DISCLOSURE MAHASISWA KOTA BANDUNG MELALUI INSTAGRAM - Shawila Nolanda Destiano Lestari; Nurru Alfi Fazri Furau'ki; Ferry Darmawan; Nurrahmawati (LPPM Stikosa - AWS, 2021)
Today's social media cannot be separated from daily activities, so that currently the penetration of social media is increasing and giving birth to a new phenomenon, namely the disclosure of one's identity or self-disclosure through social media, especially Instagram. This phenomenon encourages researchers to study the behavior of students in the city of Bandung in expressing their identity. This study used a qualitative method with a constructivist paradigm and a phenomenological approach, while determining the subject using purposive sampling technique, namely three students from three universities in Bandung and active users of Instagram. Data collection was carried out by interview and observation to strengthen research data. The results showed that self-disclosure through social media Instagram was carried out only in the open self area starting with a sense of wanting to share moments, experiences and feelings and was deemed worthy to be shared through social media. With the aim of simply sharing information with followers, while maintaining a confidential identity which is a personal identity and can lead to misunderstanding.